Fluctuation in body composition and urine specific gravity of Turkish wrestlers in a top-level official wrestling competition - Donmez, E.; Isik, O.; Baic, M. (Frontiers in Physiology, 2025)
Purpose: This research aimed to examine the fluctuations in body composition and Urine-Specific Gravity (USG) of elite wrestlers in a high-level official wrestling competition.